Przeciwdziałanie i zwalczanie małżeństw pozornych w prawie UE oraz w prawie polskim i brytyjskim - Sadowski, Piotr (Kwartalnik Prawa Publicznego, 2012)
This article concentrates upon an issue of preventing and fighting marriages of convenience concluded between EU citizens and non-EU citizens. Thus, it focuses on a tension between the necessity to respect a right to marry and the need to fight illegal immigration. In a context of the later – bearing in mind that non-EU citizens who are family members of the EU citizens are provided with a facilitated access to the territory of EU Member States – it has to be underlined that in times when some states are imposing stricter preconditions that have to be met in order to obtain visa or residence permit a marriage of convenience may be perceived by some non-EU citizens as a possibility to access the territory of the EU Member States. This is why in the article special attention is being paid to an issue of verification if a marriage is a genuine one. As this aspect of execution of a state power has been raised in jurisdiction, including jurisdiction of European Court of Human Rights, European Court of Justice and Court of Justice of the European Union, an impact of case law on EU measures and on EU Member States laws on preventing and fighting marriages of convenience is presented as well. In this regard, history of developments of legislation and administrative practices are scrutinised from a perspective of an immigration country (United Kingdom) and transit-destination country (Poland).